Epithelial Rate Difference on Donor Wound of Split Thickness Skin Graft in the Thigh Area by Applying Leukocrepe® and Medicrepe® - Rinaldi, Ivan; Sungkar, Amru; Alifianto, Untung (Indonesian Journal of Medicine, 2017)
Background: applying split thickness graft (STSG) is as one of the reconstruction techniques and it is often conducted. Applying the technique creates superficial wound on the donor wound or it is known by donor site. The elastic bandage usage is one of the tools which is used in giving treatment to donor site as a standard operational procedure treatment at Dr. Moewardi hospital (RSDM) Surakarta. RSDM Surakarta has not had clinic test yet to compare between applying elastic bandage Leukocrepe® and Medicrepe® on wound care STSG on the thigh area.Subject and Method: The study used post-test only control group design with the total of the sample was 18 patients. The study was conducted in intermediate STSG donor wound with 0.018 inches thickness on the lateral thighs. By dividing two donor wounds, a half-sided of upper part was bandaged by applying Leukocrepe® and the other half of the lower part was bandaged by Medicrepe®. After that, epithelialization score was conducted on the seventh day. All the data then were collected and after that the data were tested by applying Wilcoxon rank test.Result: according to the study conducted to 18 patients of plastic surgery section at RSUD Dr. Moewardi during November 2016-Juni 2017, the result showed that the epithelialization chart was approximately 61.39 ± 30.05% for STSG donor wound on the lateral thighs part and it was done on the seventh day by applying Leukocrepe, meanwhile applying Medicrepe, the result was approximately 43.67 ± 30.69 %. The mean score of epithelialization applying Medicrepe® was more significant than applying Leukocrepe® and it showed that there was significantly different statistically with the score (p<0.001).Conclusion: According to the result above, it can be seen that the STSG donor wound care on the thighs using Medicrepe® is more effective in accelerating epithelialization process than the one which is applied by Leukocrepe®.Key Word: Epithelization, Elastic Bandage, Medicrepe®, Leukocrepe®Correspondence: Ivan Rinaldi. Public Surgery Resident of Medical Faculty of UNS. Email: ivanmudfin@gmail.com.Indonesian Journal of Medicine (2017), 2(3): 146-153https://doi.org/10.26911/theijmed.2017.02.03.01